The moralization bias of gods' minds: a cross-cultural test. Issue 1 (3rd April 2022) - Purzycki, Benjamin Grant; Willard, Aiyana K.; Klocová, Eva Kundtová; Apicella, Coren; Atkinson, Quentin; Bolyanatz, Alexander; Cohen, Emma; Handley, Carla; Henrich, Joseph; Lang, Martin; Lesorogol, Carolyn; Mathew, Sarah; et al.
ABSTRACT: There are compelling reasons to expect that cognitively representing any active, powerful deity motivates cooperative behavior. One mechanism underlying this association could be a cognitive bias toward generally attributing moral concern to anthropomorphic agents. If humans cognitively represent the minds of deities and humans in the same way, and if human agents are generally conceptualized as having moral concern, a broad tendency to attribute moral concern—a "moralization bias"—to supernatural deities follows. Using data from 2, 228 individuals in 15 different field sites, we test for the existence of such a bias. We find that people are indeed more likely than chance to indicate that local deities care about punishing theft, murder, and deceit. This effect is stable even after holding beliefs about explicitly moralistic deities constant. Additionally, we take a close look at data collected among Hadza foragers and find two of their deities to be morally interested. There is no evidence to suggest that this effect is due to direct missionary contact. We posit that the "moralization bias of gods' minds" is part of a widespread but variable religious phenotype, and a candidate mechanism that contributes to the well-recognized association between religion and cooperation.